Tata Kelola Inklusif dalam Implementasi Program Kampung Iklim (ProKlim): Studi di Kelurahan Tabek Gadang - Yana Silva; Rifki Amanda; Rico Purnawandi Pane (JPPUMA: Jurnal Ilmu Pemerintahan dan Sosial Politik UMA (Journal of Governance and Political UMA), 2026)
Despite increasing emphasis on community-based climate adaptation, the implementation of inclusive governance in the Climate Village Program (ProKlim) remains uneven at the local level. Previous studies have primarily focused on participation and program effectiveness, while limited attention has been given to multidimensional governance inclusiveness. This study examines the implementation of inclusive governance in ProKlim at the village level in Tobek Godang Village using a qualitative case study approach. Data were collected through in-depth interviews, observation, and document analysis involving key informants from village government and community members. The findings show that inclusive governance remains fragmented and uneven. Inequalities persist in access to information and resources, participation varies across social groups, transparency tends to be symbolic, accountability remains procedural, and institutional coordination is weak. This study contributes to inclusive governance literature by demonstrating that inclusiveness in community-based climate governance is shaped by intersecting spatial, social, and institutional inequalities, producing partial and uneven inclusion rather than equal participation. The study highlights the need to strengthen institutional coordination and participatory mechanisms to support more equitable and sustainable climate governance at the village level.